Branding Regional Products through Local Identity in the Creative Industry - Syarifa Aeni MR; Firman H; Marhati Marhati; Andi Amitya Resty Dwiyanti; Muslimin Muslimin (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This study examines local identity-based branding strategies in the creative industry and their role in strengthening the competitiveness of regional flagship products in Bone Regency, South Sulawesi. Using a qualitative case study design, the research involved 18 informants, including creative MSME actors, cultural community leaders, cooperative managers, and local policymakers. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed thematically with the Miles and Huberman framework. The findings reveal that branding based on local identity is expressed through the use of natural materials, integration of the Bugis language in product names, traditional motifs in visual design, and cultural narratives embedded in digital promotion and local exhibitions]. This approach has increased product value by up to 30% and positioned Bone as a hub for culture-based creative economy. Key challenges include limited capital, weak digital infrastructure, low branding literacy, and complex trademark procedures. Conversely, opportunities arise from growing youth engagement, supportive local government policies, and integration with the tourism sector. Overall, the study underscores the importance of combining cultural preservation with modern marketing strategies to develop a sustainable creative industry that enhances regional competitiveness